Case Report: Late-Presenting Congenital Diaphragmatic Hernia With Tension Gastrothorax - Anekar, Aabha A.; Nanjundachar, Sumana; Desai, Dhaneshgouda; Lakhani, Jafferali; Kabbur, Prakash M. (Frontiers in Pediatrics, 2021)
A congenital diaphragmatic hernia (CDH) occurs when the abdominal contents protrude into the thoracic cavity through an opening in the diaphragm. The main pathology lies in the maldevelopment or defective fusion of the pleuroperitoneal membranes. Delayed diagnosis in later childhood as in the index case reported here can lead to life-threatening complications such as tension gastrothorax and gastric volvulus. Such life-threatening conditions should be managed emergently avoiding misdiagnoses and untoward harm to the patient. We report a pediatric case of an 8-year-old boy who presented with respiratory distress, chest pain, and non-bilious vomiting. He was initially diagnosed with tension pneumothorax, and the chest x-ray was interpreted as hydropneumothorax. A chest tube placement was planned but was withheld due to excessive vomiting. A nasogastric (NG) tube was placed, and a barium-filled radiograph showed an intrathoracic presence of the stomach. A diagnosis of a congenital diaphragmatic hernia with tension gastrothorax was made. The posterolateral (Bochdalek) diaphragmatic hernia was repaired successfully. This case report highlights the importance of including a late-presenting CDH in the differential diagnoses of pediatric patients who present with respiratory distress, chest pain, non-bilious vomiting, and radiological findings suggestive of tension pneumothorax.